Critical assessment issues in work-integrated learning - Ferns, Sonia; Zegwaard, K. (Asia-Pacific Journal of Cooperative Education, 2014)
© 2014, New Zealand Association for Cooperatives Education. All rights reserved. Assessment has long been a contentious issue in work-integrated learning (WIL) and cooperative education. Despite assessment being central to the integrity and accountability of a university and long-standing theories around best practice in assessment, enacting quality assessment practices has proven to be more difficult. Authors in this special issue on assessment highlight the need for balanced assessment approaches that reflect the highly variable experiences students encounter, and the need to keep validity and reliability paramount when constructing assessment structures. Increasingly quality and standards policies driven by more regulatory university environments are impacting on the design of assessment profiles. The value of workplace supervisors' feedback in WIL contexts is discussed and the challenges of measuring the nuances of unpredictable, context-dependent WIL outcomes are explored. The benefits of ePorftolios are advocated and the use of these platforms as assessment tools that enable a creative way for students to provide evidence of employability capabilities highlighted.